Polymer rheology - Han, Chang Dae (Oxford University Press, 2007)
1. Introduction. Part I Fundamental Principles of Rheology. 2. Kinematics and Stresses of a Deformable Body. 3. Continuum Theory for the Viscoelasticity of Flexible Homogeneous Polymeric Fluids. 4. Molecular Theory for the Viscoelasticity of Flexible Homogeneous Polymeric Fluids. 5. Experimental Methods for Measurement of the Rheological Properties of. Part II Rheological Behavior of Polymeric Materials. 6. Rheology of Homopolymers and Random Copolymers. 7. Rheology of Miscible Polymer Blends. 8. Rheology of Block Copolymers. 9. Rheology of Liquid-Crystalline Polymers. 10. Rheology of Thermopl.
Keywords: Polymers -- Rheology.; Polymers.; elektronické knihy; electronic books